2023
DOI: 10.1038/s41598-023-31251-1
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning analysis of correlates of mortality among patients hospitalized with COVID-19

Abstract: It is vital to determine how patient characteristics that precede COVID-19 illness relate to COVID-19 mortality. This is a retrospective cohort study of patients hospitalized with COVID-19 across 21 healthcare systems in the US. All patients (N = 145,944) had COVID-19 diagnoses and/or positive PCR tests and completed their hospital stays from February 1, 2020 through January 31, 2022. Machine learning analyses revealed that age, hypertension, insurance status, and healthcare system (hospital site) were especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A similar study in American population identified risk factors pertaining to clinical parameters, rather than laboratory-based parameters, were significantly able to classify patients based on severity. [ 18 ] Mariam Laatifi et al . [ 19 ] used Uniform Manifold Approximation and Projection (UMAP) approach with 100% accuracy, specificity and sensitivity in prognostic prediction using different ML classifiers such as XG Boost, Ada Boost, Random Forest and Extra Trees.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in American population identified risk factors pertaining to clinical parameters, rather than laboratory-based parameters, were significantly able to classify patients based on severity. [ 18 ] Mariam Laatifi et al . [ 19 ] used Uniform Manifold Approximation and Projection (UMAP) approach with 100% accuracy, specificity and sensitivity in prognostic prediction using different ML classifiers such as XG Boost, Ada Boost, Random Forest and Extra Trees.…”
Section: Discussionmentioning
confidence: 99%